Pengaruh CAR Dan NPL Terhadap ROA Pada BPR Perbarindo Cirebon - Tarjono; Gilang Bhirawa Noraga; Ujang Permana; Wawan Supriyanto (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
This research aims to analyse the influence of the Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL) on Return on Assets (ROA) within People's Credit Banks (BPR) affiliated with Perbarindo in the Cirebon region for the period 2023–2024. The study employs a quantitative approach, utilising multiple linear regression analysis on secondary data obtained from the annual financial reports of the BPR. The findings indicate that CAR has a positive and significant impact on ROA, whereas NPL has a negative and significant effect on ROA. Collectively, CAR and NPL exert a significant influence on ROA, with a coefficient of determination of 66.9%. This research provides implications for BPR management to strengthen capital and enhance credit quality.